HUBUNGAN KEKUATAN OTOT LENGAN TERHADAP HASIL SERVIS ATAS BOLA VOLI PADA SISWA PUTERA MTs NEGARA KEDUNGGALAR - Muhammad Ikhsan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the relationship between arm muscle strength and volleyball serve results. This research was conducted on male students at MTs Negara Kedunggalar. This type of research is correlation. The population in this study was 16 male students of MTs Negara Kedunggalar. The data collected in this study used arm muscle strength test instruments and volleyball service ability tests. Data analysis used correlational statistics with a significance level of 5%. The research gave the following results: there was a significant relationship between arm muscle strength and volleyball serve results. for male students at MTs Negara Kedunggalar. This is proven by the results of the analysis of the value of tcount > ttable, namely (2.942 > 2.14)